Management of Apatinib-Related Adverse Events in Patients With Advanced Osteosarcoma From Four Prospective Trials: Chinese Sarcoma Study Group Experience - Xie, Lu; Xu, Jie; Guo, Wei; Wang, Zhen; Yao, Yang; Li, Jianmin; Lin, Jianhua; Xiao, Jianru; Yu, Xiuchun; Zhang, Weibin; Cai, Zhendong; Hua, Yingqi; et al. (Frontiers in Oncology, 2021)
Four prospective trials have reported apatinib-related efficacy in osteosarcoma, with a high response rate of 43.2%. Currently, Adverse Events (AEs) have increasingly gained attention, as treatment with multiple tyrosine kinase inhibitors (TKIs) is potentially lifelong. For this reason, a consensus meeting of the Chinese Sarcoma Study Group (CSSG), which is a multidisciplinary panel composed of pediatric, medical and surgical oncologists specializing in sarcoma, nurse specialists, oncological senior pharmacists and gastroenterologists, was held to develop comprehensive guidelines on AEs emerging due to apatinib treatment to better assist in the prevention, management, and understanding of AE development. We summarized all AEs that arose in ≥10% of the participants as well as rare AEs that required extra caution to prevent that were observed in these four published prospective trials and arranged these AEs into 14 disorder systems according to CTCAE 5.0. In this review, we discuss strategies for the management of AEs in patients with advanced osteosarcoma, with the aim of maximizing treatment benefits and minimizing the need for apatinib treatment discontinuation. We also focus on providing recommendations for the prophylaxis and treatment of advanced osteosarcoma using apatinib to achieve optimal outcomes.